Towards technical development of natural dyes for the textile industry in Kenya: A case study of Bixa orellana solvent extracts - Kipruto , Abraham; Arusei, Musa; Kerich, Emmy (African Journal of Education,Science and Technology (AJEST), 2017)
The aim of the study is to develop dyes of textile fibres using the natural dyes extracted from the seeds of Bixa orellana Linn. cultivated in tropical part of the coastal region of Kenya. Natural dyes originating from plants have fiscal advantage over synthetic dyes owing to their non-allergic, non-toxic, non-carcinogenic and eco-friendly natural dyes properties. The seeds are covered by a red resin which contains a number of carotenoid compounds that constitute the main colouring agents; Bixin and Norbixin are the predominant colouring compounds. The dye was extracted using solvent extraction method. Annatto colouring compounds can be identified by (GC-MS) technique. Analyses of the essential oils were carried out using GC, GC-MS and GC co-injection (of some of the available essential oils with authentic samples) using capillary gas chromatograph Hewlett Packard (HP) 5890 A Series II equipped with a split-less capillary injector system, cross-linked Hewlett. The extract was then used to dye cellulosic fibre by Exhaustion method. Dyeing was carried out using mordants through pre and post mordant in order to compare the fastness properties of the dye. Reflectance curves of the dyed materials were made using GretagMcBeth colour Eye 700 A0spectrophotometer. From the results, the plant studied is a promising dye-yielding plant and produces a yellow orange colour.It could be exploited as a source of textile dyes and an economic plant. Additionally provide more in depth knowledge on behavior of annatto dyes and dyed cotton textile fibres.